Microalgae dewatering: Technology advancement using electrocoagulation - Uduman, N.; Danquah, Michael; Hoadley, A. (2013)
With growing sustainable development and environmental protection concerns, it islogical that renewable fuels are becoming more important. Biodiesel is an alternative topetroleum based transport fuels and it has many advantages such as a low emissionprofile. Microalgae have gained interest as a source of biomass for biodiesel production,due to the advantages of high lipid content and fast growth rates with negligiblecompetition with human food production. A major limitation with microalgae is the highenergy consumption and cost associated with current dewatering processes, and thismakes microalgae bioprocess engineering economically unattractive. Electrocoagulationis a promising dewatering process that has the potential to reduce the overall energydemand of the process.In this chapter, a batch electrocoagulation process with two marine microalgaespecies (Chlorococcum sp. and Tetraselmis sp.) and three different anode materials(aluminum, ferritic stainless steel, and carbon) is examined. The flocculation andflotation efficiency of each electrode was investigated and optimum electrocoagulationparameters were determined. A mass balance of the system was performed and thepolarity of the dissolving metal cation was determined. Power consumption and carbondioxide emissions analysis were also conducted in order to evaluate the feasibility ofcommercially applying electrocoagulation to the biodiesel production process. Resultsfrom the power consumption and carbon dioxide emission analysis showed thatelectrocoagulation requires little energy for operation, but the overall process was highlyenergy intensive due to the energy demand associated with aluminum production.However, in order to make the method more feasible for commercial use, theconsumption of electrode material has to be minimized. © 2013 by Nova Science Publishers, Inc. All rights reserved.